(untitled) (International Journal of Biology and Chemistry, 2019)
In this work, the quantitative analysis of phytochemical constituents of medicinal plant Spiraea hypericifolia L. from Kazakhstan has been made for the first time. Total bioactive components aerial and underground parts of plants material S. hypericifolia L. such as organic acids (0.28 %), (0.35 %), flavonoids (0.77 %), (5.36 %), coumarins (0.04 %), (0.21 %), saponins (2.09 %), (0.98 %), tannins (1.31 %), (1.62 %), and together with moisture content (4.72 %), (3.84 %), total ash (5.11 %), (5.41 %), were determined. Eleven macro-micro elements from the ash of plant were identified, main contents of them were Ca (362.20 μg/ml), (344.750 μg/ml), K (69.670 μg/ml), (57.8075 μg/ml), and Mg (24.270 μg/ml), (34.480 μg/ml), by using the method of multi-element atomic emission spectral analysis. In addition, twenty amino and eight fatty acids were analyzed from the plant. The results showed that major contents of amino acids were glutamate (1741 mg/100g), (1710 mg/100g), aspartate (845 mg/100g), (820 mg/100g), and alanine (560 mg/100g), (523 mg/100g), as well as in fatty acid was linoleic (81.1 %), (79.7 %) acid, respectively.